PERAN ISR DALAM HUBUNGAN ANTARA GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN - Alina Widyasari; Taufikur Rahman (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This study aims to identify and analyze the Impact of Green Accounting Implementation and Evironmental Performance on Financial Performnce with Ilamic Socil Reporting as an Intervening Variable in Jakarta Islamic Index(JII) 70 Companies 70 Period 2019-2021. This type of research with secondary data formed by panel data. Data collection technique with purpose sampling technique.the sampel used was 22 companies registered in JII 70 for the 2019-2021 period. Data obtained from the company’s Annual Report accessed through the website www. Idx.co.id. the analytical method used in descriptive test, stationarity test, R2 test, F test and T tes, classical assumption test, Sobel test, and Path test. The results of this study indicate this green accounting variables, Islamic Social Reporting (ISR) have a significant positive effect on financial performance, environmental performance variables have a significant negative effect on financial performance. Based on the Sobel Test and Path analysis test, it shows that the Islamic Social Reporting (ISR) variable cannot mediate the effect of green acconting and environmental performance on financial performance.